2020
DOI: 10.1088/1757-899x/928/7/072008
|View full text |Cite
|
Sign up to set email alerts
|

Study the contamination of Radioactivity levels of 226Ra, 232Th and 40K in (water)Iraq and their potential radiological risk to human population

Abstract: In this study, the level of natural radioactivity in the banks of the Euphrates River was evaluated of four sites for the passage of the Euphrates(Al Kufa, Abu Sukhair, Al Mishkhab and Al Qadisiyah), as samples were collected along the Euphrates River within the province of Najaf. The radioactivity of naturally formed radioactive materials of Uranium-238 and Thorium-232 series soluble strands in addition to the Potassium -40 radioisotope was determined using the NaI (Tl) sodium iodide reagent system (3"x3"). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The level AED from ingestion of water has been shown to vary by countries. Different studies in the same countries; Nigeria [ 30 , 31 ], Ghana [ 12 , 32 ] and Iraq [ 33–35 ] also had varying results. The result from the current study is higher than the results reported from Ghana (13:32), Nigeria [ 30 ], Egypt [ 36 ], Saudi Arabia [ 37 ], Malaysia [ 38 ] and Iraq [ 35 ] but lower than the results from Brazil [ 39 ], Nigeria [ 31 ] and Iraq [ 33 , 34 ].…”
Section: Results and Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level AED from ingestion of water has been shown to vary by countries. Different studies in the same countries; Nigeria [ 30 , 31 ], Ghana [ 12 , 32 ] and Iraq [ 33–35 ] also had varying results. The result from the current study is higher than the results reported from Ghana (13:32), Nigeria [ 30 ], Egypt [ 36 ], Saudi Arabia [ 37 ], Malaysia [ 38 ] and Iraq [ 35 ] but lower than the results from Brazil [ 39 ], Nigeria [ 31 ] and Iraq [ 33 , 34 ].…”
Section: Results and Disscussionmentioning
confidence: 99%
“…Different studies in the same countries; Nigeria [ 30 , 31 ], Ghana [ 12 , 32 ] and Iraq [ 33–35 ] also had varying results. The result from the current study is higher than the results reported from Ghana (13:32), Nigeria [ 30 ], Egypt [ 36 ], Saudi Arabia [ 37 ], Malaysia [ 38 ] and Iraq [ 35 ] but lower than the results from Brazil [ 39 ], Nigeria [ 31 ] and Iraq [ 33 , 34 ]. Although the AED from the ingestion of water (AED w ) from this study is above the guidance level of WHO, it is within the range of values reported in literature.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…Al-Khashab et al 16 measured the pH, TDS, and EC and discovered that they were 7.7-8.7, 226-302 mg/L, and 330-405 μs/cm, respectively, and that all the values are within the recommended ranges. Salman et al 17 were able to carry out a comprehensive radioactivity of 232 Th, 238 U, and 40 k. The NaI(Tl) detector was used to ascertain this. The researchers found that the lifetime risk of cancer was much lower than what the ICRP had determined, which means the samples are safe and healthy.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the values of concentration of these elements were less than the global limit. Salman and his group [15] were able to carry out comprehensive radioactivity levels of 232 Th, 238 U, and 40 k. The NaI (Tl) detector was used to ascertain this. The researchers found that the lifetime risk of cancer was much lower than what the ICRP had determined, which means that the samples are safe and healthy.…”
Section: Introductionmentioning
confidence: 99%